2019
DOI: 10.3233/jad-190299
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Band Light Stimulation in Human Case Studies: Groundwork for Potential Alzheimer’s Disease Treatment

Abstract: Background: It is known that proteins associated with Alzheimer's disease (AD) pathogenesis are significantly reduced by 40 Hz entrainment in mice. If this were to translate to humans, verifying that such a light stimulus can induce a 40 Hz entrainment response in humans and harnessing insights from these case studies could be one step in the development of a multisensory device to prevent and treat AD. Objective: Verify the inducement of a 40 Hz response in the human brain by a 40 Hz light stimulus and obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…While stimulating the brain with 40Hz auditory or visual stimuli is referred to as entrainment, our results show that such stimulation does not necessarily cause notable entrained oscillatory activity in all brains. Based on earlier studies on entrainment 31,33,37 , a clear response of the brain to the stimulant frequency is expected as a peak in the spectrogram of the recorded response on that frequency. Accordingly, we propose a method to determine the occurrence of entrainment (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While stimulating the brain with 40Hz auditory or visual stimuli is referred to as entrainment, our results show that such stimulation does not necessarily cause notable entrained oscillatory activity in all brains. Based on earlier studies on entrainment 31,33,37 , a clear response of the brain to the stimulant frequency is expected as a peak in the spectrogram of the recorded response on that frequency. Accordingly, we propose a method to determine the occurrence of entrainment (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Interventions based on stimulating neural populations in the gamma band have been recently proposed and are under examination on animal models of AD 22,[27][28][29] and in limited human studies [30][31][32][33][34][35][36] . These approaches aim to reinvigorate the functionality of the brain networks through synchronized pumping of rhythmic energy via one or multiple sensory modalities.…”
Section: Introductionmentioning
confidence: 99%
“…A functional magnetic resonance imaging (fMRI) study measured the real-time response of the brain to flickering visual stimuli with a frequency varying from 1 to 40 Hz, and revealed that visual stimuli could selectively activate cortical areas and regulate specific brain connections ( Chai et al, 2019 ). In another ERP study, it was verified that 40, 60, and 80-Hz light stimulation induced the human brain response, and the greatest amplitude was always found in the primary visual cortex ( Jones et al, 2019 ). However, these studies did not show changes in the hippocampus or determine whether there were changes in brain activity related to memory tasks.…”
Section: Introductionmentioning
confidence: 87%
“…A 40 Hz light flicker paradigm has also been explored in humans, demonstrating widespread 40 Hz entrainment (222), but a study in AD patients found no reduction of Aβ pathology as analyzed by PET (223). Further studies are required to evaluate the possible role of noninvasive direct cell modulation in human patients.…”
Section: Direct Cell Modulationmentioning
confidence: 99%